2021
DOI: 10.1038/s41467-021-23165-1
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourced mapping of unexplored target space of kinase inhibitors

Abstract: Despite decades of intensive search for compounds that modulate the activity of particular protein targets, a large proportion of the human kinome remains as yet undrugged. Effective approaches are therefore required to map the massive space of unexplored compound–kinase interactions for novel and potent activities. Here, we carry out a crowdsourced benchmarking of predictive algorithms for kinase inhibitor potencies across multiple kinase families tested on unpublished bioactivity data. We find the top-perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 49 publications
5
51
0
Order By: Relevance
“…However, 20% of drug combinations remained poorly predicted by all the methods, regardless of the method category. This is consistent with other DREAM Challenges, where it has been observed that the specific prediction algorithm per se is not the critical component, rather how the algorithm is used in practice and based on what information often defines the best-performing computational methods for many prediction tasks in biomedical research [18] , [19] .
Fig.
…”
Section: Resultssupporting
confidence: 87%
“…However, 20% of drug combinations remained poorly predicted by all the methods, regardless of the method category. This is consistent with other DREAM Challenges, where it has been observed that the specific prediction algorithm per se is not the critical component, rather how the algorithm is used in practice and based on what information often defines the best-performing computational methods for many prediction tasks in biomedical research [18] , [19] .
Fig.
…”
Section: Resultssupporting
confidence: 87%
“…( Table 1 ). In general, consistent with prior results on the value of evidence integration, 25 overall performance was positively correlated with the number of additional databases utilized in the analysis, accounting for 27% of the variance in SC1 and a remarkable 82% of the variance in SC2.…”
Section: Resultssupporting
confidence: 86%
“…Teams were further encouraged to use public data sources, such as the Cancer Cell Line Encyclopedia, 21 the Genomics of Drug Sensitivity in Cancer database, 22 and the CMap L1000 database, 23 and to leverage insights and models developed in previous DREAM Challenges. 8 , 19 , 24 , 25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several artificial intelligence (AI) methods for drug repurposing are based on DTIs as well as chemical structural similarities [13][14] [15]. However, these methods are applied only on selected set of compounds resulting in limited prediction outcomes [13].…”
Section: Introductionmentioning
confidence: 99%